Local herbs for pain relief in the area of Tumbon Khao Hin Son, Chachoengsao, Thailand - VACHIRAPORN PIKULTHONG; SUPAMAS BHIROMPAN; MANUSSAWEE DECHKLA; KANLAYA MOKKAPAN; NARUMON BOONMAN; CHANATE WANNA; KWANCHAYANAWISH MACHANA; SIRIRAT PHAKPAKNAM (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Pikulthong V, Bhirompan S, Dechkla M, Mokkapan K, Boonman N, Wanna C, Machana K, Phakpaknam S. 2022. Local herbs for pain relief in the area of Tumbon Khao Hin Son, Chachoengsao, Thailand. Biodiversitas 23: 5012-5019. Local herbs have been used in Thailand for years. However, data collection on the use of local herbs in particular areas has not been thorough. This study aimed to survey local herbs treating pain relief in the area of Tumbon Khao Hin Son, Amphoe Phanom Sarakham, Chachoengsao, Thailand. Semi-structured interviews were used. Purposive sampling was used to determine the sample group. In the survey and study on botanical characteristics, from November 2019 - March 2020, 68 plants were identified and classified into 29 families. The local herbs which were mostly used for pain relief included 7 species from the Acanthaceae family, 6 types from Fabaceae, Lamiaceae, and 5 types from Zingiberaceae. The leaves of herbaceous plants had the highest frequency of use. A remedy, Ko-Klan, was found and prepared using a boiling method that could relieve pain. The surveyed herbs were used to treat 4 main symptoms which were body pain, stomachache, headache, and toothache. It was found that 36 species of herbs, or a majority of them, were used to directly relieve the pain. The interviews showed that 27% of the respondents had some home-grown herbs which were used for cooking and basic illness treatment. The age of the respondents was relevant to the use of herbs. The findings in this study will be the foundation for local herb studies which support and are aware of Thai local wisdom and knowledge as guidance to alter herbs for pharmaceutical purposes in the future.